Why does life-writing talk about science?: Foucault, Rousseau, and the early journal intime - Ferguson, S (University of Hawaii Press, 2017)
This article examines the reasons why life-writing makes use of discourses from the natural sciences. It focuses on the emergence of autobiography and the journal intime in France at the moment of a fundamental shift towards the modern episteme (identified by Foucault), which is both historical and person-centred.